Down-regulation of COX-2 activity by 1α,25(OH)2D3 is VDR dependent in endothelial cells transformed by Kaposi's sarcoma-associated herpesvirus G protein-coupled receptor - Tapia, Cinthya Mariela (2020)
Our previous reports showed that 1α,25-dihydroxyvitamin D3 (1α,25(OH)2D3) has antiproliferative actions in endothelial cells stably expressing viral G protein-coupled receptor (vGPCR) associated with the pathogenesis of Kaposi's sarcoma. It has been reported that COX-2 enzyme, involved in the tumorigenesis of many types of cancers, is induced by vGPCR. Therefore, we investigated whether COX-2 down-regulation is part of the growth inhibitory effects of 1α,25(OH)2D3. Proliferation was measured in presence of COX-2 inhibitor Celecoxib (10–20 μM) revealing a decreased in vGPCR cell number, displaying typically apoptotic features in a dose dependent manner similarly to 1α,25(OH)2D3. In addition, the reduced cell viability observed with 20 μM Celecoxib was enhanced in presence of 1α,25(OH)2D3. Remarkably, although COX-2 mRNA and protein levels were up-regulated after 1α,25(OH)2D3 treatment, COX-2 enzymatic activity was reduced in a VDR-dependent manner. Furthermore, an interaction between COX-2 and VDR was revealed through GST pull-down and computational analysis. Additionally, high-affinity prostanoid receptors (EP3 and EP4) were found down-regulated by 1α,25(OH)2D3. Altogether, these results suggest a down-regulation of COX-2 activity and of prostanoid receptors as part of the antineoplastic mechanism of 1α,25(OH)2D3 in endothelial cells transformed by vGPCR.